2011
DOI: 10.1007/s10812-011-9486-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of neural networks for classification of biological compounds from the characteristics of whispering-gallery-mode optical resonance

Abstract: We have analyzed the feasibility and expediency of using a probabilistic neural network as a classifier for processing and interpreting data obtained using a biosensor we have developed that is based on whisperinggallery-mode optical resonance. We have established that the probabilistic neural network makes it possible to correctly classify the biological compounds under study with average 97.3% probability.Introduction. Development of intelligent systems based on artificial neural networks to solve problems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…We have used several schemes of experimental realization of the method [6][7][8][9][10]. Here the newer versions of the scheme have been developed (Fig.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used several schemes of experimental realization of the method [6][7][8][9][10]. Here the newer versions of the scheme have been developed (Fig.1).…”
Section: Methodsmentioning
confidence: 99%
“…Improved methods of nanoparticle synthesis based in particular on ultrafast laser ablations directly in biocompatible liquids and different materials under laser-induced synthesis can frame conditions for functionalizing and fragmentation of nanoparticles within a single process step and combine it with aggregate formation. On the other hand recently developed tools for data processing can realize real-time identification of biological agents [6][7][8][9]. So combining advantages of plasmon enhancing optical microcavity resonance with identification tools can give a new platform for ulta sensitive label-free biomedical sensor, which can be used for cellular and tissue imaging for diagnostics, blood components monitoring, drug monitoring and targeted drug delivery, remote control for detection, treatment and destruction of cancer, nanolaser for nanosurgery etc.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing controlled amount of nano particles (50 nm in diameter glass gel solution) into microsphere surrounding was accompanied also by correlative resonance shift. The most attention was concentrated on development of a technique for recognition and identification of nanoparticles and biomolecules in liquid fluids [8][9][10][11][12]. We demonstrated that the only spectral shift is not sufficient for identification of biological agents by developed approach.…”
mentioning
confidence: 99%
“…We demonstrated that the only spectral shift is not sufficient for identification of biological agents by developed approach. So classifier based on probabilistic neural network for biological agents and micro/nano particles classification has been developed [8][9][10][11][12]. It was tested on solutions of different biological agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation